Diagnosing and Treating Depression in Older and Oldest Old - Morichi, V.; Dell’Aquila, G.; Trotta, F.; Belluigi, A.; Lattanzio, F.; Cherubini, A. (Current Pharmaceutical Design, 2015)
Depression is very common in older people and it is associated with negative consequences such as functional decline, increased morbidity and mortality and higher healthcare costs. Despite this, it is still underdiagnosed and undertreated and the issue is particularly relevant for people older than 80 years. The main reasons for underdiagnosis are: atypical presentation, concomitant cognitive decline, inadequate diagnostic tools, and prejudice that depression is a normal part of ageing. On the other hand, the main reasons for undertreatment are: multimorbidity, concerns about adverse events and drug interactions, lack of confidence in the efficacy and safety of pharmacological and non-pharmacological treatments in the oldest old depressed patients, who are underrepresented in clinical studies. The new antidepressants are the drugs most frequently used, due to their perceived more favorable safety profile than older antidepressants. Psychotherapy is equally effective but less frequently used and should request some adaptive strategies for the peculiarities of octogenarians. Electroconvulsive therapy is limited to severe psychotic late-life depression resistant to other treatments. In light of the heterogeneity of people aged 80 years and over, with multiple and different medical, functional, socioeconomic problems, a multidimensional approach is probably the most suitable both for diagnosis and treatment, in order to develop an individualized care plan. These considerations should guide the formulation of future research studies, specifically tailored for the oldest depressed patients.
Keywords: Depression